Science and art of ductile grinding of brittle solids. (February 2021) - Huang, Han; Li, Xuliang; Mu, Dekui; Lawn, Brian R.
Abstract: Prior to any practical application, brittle material components may need to be machined to a high degree of precision in order to avoid functional breakdown as well as to maintain exacting surface dimensional integrity and retain strength. This usually means grinding in the ductile region. Optimization of the grinding process can shorten manufacturing time and cost and prolong component lifetime. This article reviews the current state of the art of ductile grinding and outlines the underlying science behind pertinent machining events. Engineering aspects of the grinding process will be surveyed, with consideration of wheel requirements and of such variables as grit characteristics, strain rate and temperature. Attention will be given to the fundamental role of removal processes from individual and cumulative microcontacts, using nanoscratch mechanics as the underlying basis for analysis. The critical influence of diversity in material microstructures in determining local deformation mechanisms and subsequent material removal will be highlighted. Practical requirements for optimal ductile grinding will be indicated. Graphical abstract: Image 1 Highlights: This review presents a novel perspective of ductile grinding, in terms of a basic materials-based foundation. It outlines the fundamentals of brittle-ductile transitions and identifies attendant removal mechanisms of brittle solids. It summarizes important aspects of ductile grinding, including machine system, wheel integrity, and grinding variables. It offers practical considerations for future development of ductile grinding.